Optimalisasi Nanopartikel Lipid Eksopolisakarida Termodifikasi Asam Folat untuk Penghantaran Trastuzumab Biosimilar Target HER2 pada Kanker Payudara - I Kadek Ari Sanjaya; Baiq Bunga Citra Pratiwi (Faculty of Medicine, Universitas Mataram, 2026)
Breast cancer remains a leading cause of cancer-related mortality, with HER2-positive subtypes accounting for 20-30% of cases. While trastuzumab has revolutionized treatment, its efficacy is limited by poor tumor penetration, systemic toxicity, and high costs. This literature review explores folic acid-modified exopolysaccharide lipid nanoparticles (FA-EPS-LNPs) as a novel delivery system for trastuzumab biosimilar. Exopolysaccharides offer biocompatibility and biodegradability, while lipid nanoparticles protect therapeutic proteins and enhance cellular uptake. Folic acid conjugation enables dual targeting through folate receptors overexpressed in cancer cells and HER2-specific activity. The review examines physicochemical properties, optimization parameters including particle size, surface charge, encapsulation efficiency, and folic acid conjugation methods. Evidence demonstrates enhanced cellular uptake, improved cytotoxicity, reduced off-target effects, and superior pharmacokinetics compared to conventional formulations. Challenges include scale-up manufacturing, stability, immunogenicity, and regulatory considerations. This review identifies knowledge gaps and highlights FA-EPS-LNPs' potential to improve treatment outcomes, reduce costs, and enhance patient quality of life in HER2-positive breast cancer therapy.